Acknowledgment to Reviewers of Pharmaceuticals in 2020 - Pharmaceuticals Editorial Office (Pharmaceuticals, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Pharmaceuticals maintains its standards for the high quality of its published papers [...]